CDF data of cosmic noise absorption measured with the 30 MHz broad-beam riometer at Husafell, Iceland. - Kazuo Shiokawa; ISEE IUGONET Metadata Management Group (名古屋大学, 2017)
Cosmic Noise Absorption (CNA) measured at 1-sec intervals with the 30 MHz broad-beam riometer at Husafell, Iceland. The data are distributed in the Common Data Format (CDF). dataset